The Urgency of Research and Strengthening Entrepreneurship Policies in Generating Business Models in Ex-Conflict Areas - Suadi Zainal (Universitas Teuku Umar, 2022)
Entrepreneurship contributes a lot to the economic growth of a regional area. In former conflict areas, entrepreneurship is a mechanism to facilitate prosperity and peace. The involvement of former conflict actors in micro, small and medium enterprises (MSMEs) provided them opportunities to enjoy peace dividends and repair the order of life damaged by prolonged conflict. Even so, failure of MSMEs become a problem because it causes economic stagnation and has the opportunity to create new conflict. Therefore, this paper aims to analyze the importance of research and strengthening policies related to entrepreneurship in former conflict areas. This study was conducted in Aceh Utara District using a qualitative approach. The data collection process carried out observation, interviews, and document studies. The empirical facts were analyzed by the stage of data reduction and data categorization, data display, and conclusion. The results showed that one of the causes of failure in MSMEs developments is weak policies and regulations related to community business empowerment. This fact was raised because the policies presented by the stakeholders were not based on research. Indeed, strengthening policies related to MSMEs can be done by making the results of studies and social mapping the primary basis for policymaking. Thus, the development of the MSMEs model for former conflict actors in Aceh has effects on increasing welfare and maintaining sustainable peace.